Interaksi Teman Sebaya dan Gaya Belajar Siswa terhadap Prestasi Belajar Biologi Kelas X SMA Negeri 7 Pekanbaru - Awal, Raudhah; Sari, Martala; Amalia, Tuti (Indonesian Biology Teachers, 2018)
Abstract. This study aimed to determine the relationship between the peer interaction and learning styles towards learning achievement biology class X SMA Negeri 7 Pekanbaru in Academic Year 2016/2017. This study held on mei 2017. This study was correlational. The population in this research was 250 students with samples in this study were 71 students of class X were selected by simple random sampling technique. Data analysis technique used Pearson Product Moment Correlation. Based on data analysis, r value peer interactions on learning achievement was 0.570 and the r2 percentage was 32.8% means that there was a positive relationship. r value learning styles to the learning achievement was 0.151 and The r2 percentage was 2.1%, means that there was a positive relationship and r value multiple correlation coefficient between the peer interactions and learning styles was 0.575 and the R Square percentage was 33.1% its means that there was a positive that the relationship of peer interaction and learning styles of biology student learning. Test values obtained F significant correlation coefficient was 16.830 and F table was 3.13, then Fh (16.830) > Ft (3.13). Reject H0, which means there was a significant relationship between the peer interaction and learning styles towards learning achievement of biology at the class X of SMA N 7 Pekanbaru in Academic Year 2016/2017.Â Keywords: peer interaction, learning styles, and learning achievement